Risk factors for diabetes in recently arrived migrants in Scania, Sweden compared to the general population - Zdravkovic, Slobodan; Grahn, Mathias; Mangrio, Elisabeth; Rämgård, Margareta; Annersten Gershater, Magdalena (Frontiers in Public Health, 2025)
IntroductionThe prevalence of type 2 diabetes has increased worldwide, where the highest prevalence has been found in the Eastern Mediterranean region. Effective measures must be taken to prevent or delay the occurrence of type 2 diabetes and its complications. The present study aimed to investigate the correlation between factors linked to risk for diabetes, individually and cumulatively, and established diabetes in recently arrived migrants from Iraq and Syria in Scania and compare it to the rest of the population.MethodA cross-sectional survey was used to compare data between a sample of recently arrived migrants and a sample from the rest of the population in Scania, Sweden.ResultsThe prevalence of self-reported diabetes was significantly higher among recently arrived migrants (6.9%) compared to the rest of the population (4.9%). High blood-pressure, unhealthy weight, physical inactivity, and older age increased the risk for self-reported diabetes solely but also cumulatively.ConclusionIt is important to identify individuals with a high risk of diabetes and put preventive efforts into combating risk factors for diabetes. Targeting specific risk factors significantly reduces the risk of developing this disease.